(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Introduction: Total Knee arthroplasty remains the most commonly performed surgical procedure for the management of knee osteoarthritis when conservative management fails. Apart from pain relief, improved range of motion and improvement in lifestyle of the patient are major advantages. Long term follow-up of total knee arthroplasty has shown up to 97% survival rates at 15 and 20 years (Buechel 2002, Callaghan et al. 2005). With newer implants providing longer survivorship, it is crucial to study long term functional outcome in patients to have a better understanding of the variables responsible for providing good outcome. We conducted the study to evaluate the functional outcome following Posterior Stabilized Total Knee Arthroplasty without patellar resurfacing at 2-year follow-up. Material and Methods: We have prospectively studied functional outcome for 2 years in terms of Knee Society Scoring System in 114 patients undergoing total knee arthroplasty without patellar resurfacing for knee osteoarthritis in the Department of Orthopedic Surgery Unit 1 between June 2020 and January 2022. Following approval of the Ethical committee, 114 patients presenting with advance stage of knee osteoarthritis after failed conservative management, underwent Total Knee arthroplasty without patellar resurfacing. Knee Society Scoring was calculated pre-operatively and post-operatively at 6weeks, 6, 12 and 24 months. Difference between means Knee Society Score at each follow-up was assessed by paired sample T-test. For statistical significance P-value of ? 0.05 was selected. Results: The study consisted of 114 patients of which 2 died and 2 were lost to follow up and were thus excluded. There were 64 (56.1%) males and 46 (40.4%) female patients with mean age of 58.14±9.50 years ranging from 30 to 77 years. In total, 56 (49.1%) were operated on the right and 54 (47.4%) operated on the left. Mean operative time for the surgery was 79.2±14.0 minutes. Pre-operatively, mean Knee score and Knee functional score was 38.6±13.92 and 43.0±18.2 respectively. The mean Knee score and Knee Functional score at was 51.4±19.6 and 56.5±14.5 at post-operative 6 weeks, 81.6±6.6 and 82.6±7.2 at 6 months, 88.6±3.8 and 89.1±3.5 at 12 months, 89.7±3.6 and 90.1±2.9 at 24 months. A total of 4 (3.5%) patients developed post-operative complications which were managed accordingly. There was significant improvement in the knee score and the functional score pre-operatively when measured at 24 months post-operatively with p value < 0.05. Conclusion: Our study concludes that significantly good results can be obtained in Posterior Stabilized Total Knee without Patellar Resurfacing at two years follow-up in terms of Functional outcome using the Knee Society Scoring System.